A physiological perspective of the associations between hydration status and CTP neuroimaging parameters in hyper‐acute ischaemic stroke patients. (9th February 2021) - Buoite Stella, Alex; Ajčević, Miloš; Furlanis, Giovanni; Lugnan, Carlo; Gaio, Marina; Cillotto, Tommaso; Scali, Ilario; Caruso, Paola; Cova, Maria Assunta; Naccarato, Marcello; Manganotti, Paolo
Abstract: Hypohydration may be associated with vascular diseases, poor prognosis and worse outcomes in stroke. The underlying mechanisms have not yet been completely investigated, although some studies suggested potential associations with brain perfusion and collaterals status. Despite the potentially different mechanisms promoting serum or urine biomarkers of hypohydration, few studies have investigated both markers separately. A prospective descriptive study was conducted in stroke patients admitted to a stroke unit <4.5 h from symptoms onset. All patients underwent neurological evaluation and whole‐brain computed tomography perfusion (CTP) upon admission. Blood and urine samples were immediately collected at admission, and patients were defined as "hypohydrated" (HYP) if blood urea nitrogen‐to‐creatinine ratio was >15 and "underhydrated" (UND) if urine osmolality was >500 mOsm/kg. CTP images were processed to calculate core, penumbra, their mismatch and total hypoperfused volume. Forty‐six patients were included and were grouped according to hydration status. Despite no different NIHSS at baseline, at CTP HYP was independently associated with core‐penumbra mismatch ( β : −0.157, 95% CI: −0.305 to −0.009; p = .04), while UND was independently associated with the total hypoperfused volume ( β : 31.502, 95% CI: 8.522‒54.481; p = .01). Using CTP imaging, this study proposes a physiological insight of some possible mechanisms associated with the better outcomes observed in acute stroke patients when properly hydrated. These results suggest different associations between hydration status and CTP parameters depending on serum or urine biomarkers in the hyper‐acute phase and encourage the association between hydration status and stroke characteristics.